FAKTOR DETERMINAN PENCEGAHAN POTENSI PENULARAN TB PARU PADA KELUARGA DI WILAYAH KERJA PUSKESMAS KAR-TINI KOTA PEMATANG SIANTAR TAHUN 2023 - Nasution, Erizal Salam Putra; Sarma, Amelia; Lubis, Ayu Zulhafni; Tarigan, Beti Susanti; Putri, Dian Primadia; Ariescha, Putri Ayu; Fentiana, nina (Fakultas Kedokteran, Institut Kesehatan Deli Husada Deli Tua, 2024)
Pulmonary TB is ranked as the 10th largest disease in all Pematang Siantar city health centers with a total of 546,324 cases (57.8%).The Kartini Health Center in Pematang Siantar City in 2019 there were 13 people with pulmonary TB, in 2020 there were 15 people, while in 2021 there were 28 people and an increase in 2022 for the October period as many as 49 people.The purpose of this study was to analyze the determinants of potential prevention of pulmonary TB transmission in families.The type of research used is analytic quantitative with a cross sectional design, the number of samples is 44 people.Data collection using a questionnaire.Data analysis used univariate analysis and bivariate analysis with the Chi-Square test.The results showed that the knowledge of pulmonary TB sufferers was in the good category by 50.0%, the attitude was in the good category by 54.5%, the ventilation category was eligible by 52.3%, the coaching of health workers was in the good category by 52.3%, the family support was in the good category by68.2%, prevention of the potential transmission of pulmonary TB in the family is 59.1%.The head of the Puskesmas should carry out socialization or counseling regarding efforts to prevent and control pulmonary TB disease, especially for those around TB patients by involving health cadres, RT, RW, religious leaders, and youth organizations.